ANALISIS COST VOLUME PROFIT SEBAGAI ALAT BANTU EVALUASI PENCAPAIAN LABA PADA PT NAUMAN LANDMARK GROUP JAKARTA - Lasimun Lasimun; Riska Apriani; Rony Setiawan (POLITEKNIK LP3I JAKARTA, 2019)
This study aims to determine the calculation of income statements that are in accordance with accounting science, the calculation of minimal sales so that the company does not suffer losses, and evaluate the achievement of the overall profit of the housing Amanila Residence Depok by using a cost-volume-profit (CVP) analysis in 2017, with a starting point from the background of competition and cluster housing growth that is increasingly mushrooming in Depok. The object of this research is PT Nauman Landmark Group which is located at Jalan Pejaten Barat II Number 23A Pasar Minggu, South Jakarta. This research focuses on determining profits and other matters related to earnings planning such as break even points, margin of safety, and the company's minimum sales. In the preparation of this study, the analysis used is to use mathematical methods. The results of this study indicate that PT Nauman Landmark Group in 2017 earned a profit of Rp.14,996,255,337.50, if there were no changes in selling prices and no increase in costs. PT Nauman Landmark Group Jakarta must pay attention and take action according to predictions or estimates, for a total cost of Rp.5,393,444,663.00 with a variable cost of Rp.4,443,202,163.00 and a fixed cost of Rp.950,242,500.00. Based on the calculation of cost-volume-profit analysis (CVP), it shows that the Amanila Residence Depok housing estate has evaluated the achievement of profit well because the amount of realized profit is greater than the planned profit amount.Keywords: Profit, Break Even Point, Margin of Safety, cost-volume-profit (CVP).